Potensi Wisata Halal di Desa Rindu Hati Kabupaten Bengkulu Tengah Menggunakan Pendekatan Porter Five Forces - Prisiliko, Olivia; Yunus, Fatimah; Stiawan, Evan (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2022)
The goal of this research is to figure out how the potential for halal tourism in Rindu Hati Village, Central Bengkulu Regency uses the Porter Five Forces approach. The research used a qualitative technique and was a sort of field research (field research). It may be concluded based on the study's findings that first, tourism in Rindu Hati Village, Rindu Hati Village Tourism has the potential as a halal tourist destination because it has fulfilled several indicators that have been considered, such as available halal food and drinks, prayer rooms, Qibla directions, proper washing places, toilets men and women are separated, there is a prohibition on activities that violate sharia norms to provide comfort for tourists, especially Muslim tourists. Second, Porter Five Forces results that tourism in Rindu Hati Village has good product differentiation, requires large capital to enter, and even competes with facilities that are by halal tourism indicators, bathing places are a threat to substitute products but tourism in Rindu Hati Village still has providing tubing services, the bargaining power of suppliers since the do not have a major influence the relationship is only limited to sellers and buyers without a contract, and there is no bargaining with tourists because it is the final price.